Internationalizing the National University - Elizabeth Buckner (Gulf Education and Social Policy Review)
Abstract This article, which is a translated excerpt from the book Degrees of Dignity: Arab Higher Education in the Global Era, focuses on internationalization of higher education in the Arab Middle East and North Africa. It puts recent transformations in Gulf countries in perspective historically and regionally. The chapter discusses how trends towards internationalization are affecting higher education systems in the region, through both international student mobility, campus partnerships and branch campuses. The article argues that internationalization efforts can are popular to the extent that they create more opportunities for youth, but can also be problematic when they are limited to an elite few or are exclusively oriented towards the West.